Prospective clinical evaluation of a LightCyclerTM-mediated polymerase chain reaction assay, a nested-PCR assay and a galactomannan enzyme-linked immunosorbent assay for detection of invasive aspergillosis in neutropenic cancer patients and haematological stem cell transplant recipients - Buchheidt, Dieter; Hummel, Margit; Schleiermacher, Dietlind; Spiess, Birgit; Schwerdtfeger, Rainer; Cornely, Oliver A.; Wilhelm, Stefan; Reuter, Stefan; Kern, Winfried; Südhoff, Thomas; Mörz, Handan; Hehlmann, Rüdiger (British journal of haematology, 2004)
Invasive aspergillosis (IA) is a considerable clinical problem in neutropenic patients with haematological malignancies but its diagnosis remains difficult. We prospectively evaluated a LightCyclerTM polymerase chain reaction (PCR) assay, a nested-PCR assay and a galactomannan (GM) enzyme-linked immunosorbent assay (ELISA) to validate their significance in diagnosing IA. During 205 treatment episodes in 165 patients from six centres, a nested-PCR assay and GM testing was performed at regular intervals. Positive nested-PCR results were quantified by a LightCyclerTM PCR assay. Patient episodes were stratified according to the 2002 European Organization for Research and Treatment of Cancer/Mycosis Study Group consensus criteria and the PCR and serology results were correlated with the clinical diagnostic classification. Sensitivity and specificity rates for the nested-PCR assay were up to 63·6% [95% confidence interval (CI): 30·8-89%) and 63·5% (95% CI: 53·4-72·7%) respectively, and 33·3% and 98·9% (95% CI: 7·5-70·1% and 94·2-99·9%) for GM respectively. The LightCyclerTM PCR assay yielded positive results in 21·4%, lacking discrimination by quantification across the different clinical categories. In this prospective comparison, PCR was superior to GM with respect to sensitivity rates. In patients at high risk for IA, positive results for Aspergillus by PCR of blood samples are highly suggestive for IA and contribute to the diagnosis.